Clinical effect of channel assisted cervical key hole technology combined with ultrasonic bone osteotome in the treatment of single segment cervical spondylotic radiculopathy - Liu, Junlin; Kong, Qingquan; Feng, Pin; Zhang, Bin; Hu, Yuan; Ma, Junsong (Frontiers in Surgery, 2022)
Objective: To explore the clinical effect and operating skills of channel assisted Cervical Key Hole technology combined with Ultrasonic Bone Osteotome (CKH-UBO) in the treatment of single segment cervical spondylotic radiculopathy (CSR). Methods: From June 2018 to June 2020, 14 patients diagnosed with CSR and treated with channel assisted CKH-UBO were collected. The duration of the disease, the length of the incision, the operation time, the amount of bleeding during the operation, the length of hospitalization and the complications were recorded. The Range Of Motion (ROM) and the stability of the surgical segment were recorded before and after the operation. Visual analog scale (VAS), neck disability index (NDI) and modified macnab efficacy evaluation criteria were used to evaluate the surgical efficacy. Results: The operative segments of the enrolled patients were all lower cervical vertebrae. The average incision length was 2.0±0.1cm, the operation time was 42.2±5.7 minutes, the intraoperative bleeding volume was 32.7±4.1ml, and the hospital stay was 5.6±1.2 days. There was no difference in ROM between preoperative and 3 months and 1 year after operation (P > 0.05), and all patients did not have segmental instability. The VAS scores of neck pain before surgery, 3 days after surgery, 3 months after surgery, and 1 year after surgery were 5.6±1.2, 1.6±0.6, 1.1± 0.7, 0.6 ± 0.5, and the VAS scores of upper limb pain were 6.2±1.2, 1.7±0.7, 1.1 ±0.6, 0.6±0.5. The NDI scores of upper limb pain before surgery, 3 days after surgery, 3 months after surgery, and 1 year after surgery were 36.7±3.5, 9.8±2.4, and 3.9±1.5, 1.8±1.0, The VAS and NDI scores at all follow-up time points after operation were significantly lower than those before operation (P < 0.001). One year after operation, the curative effect was evaluated according to the modified macnab evaluation standard, and the excellent and good rate was 100%. The complication rate was 6.25%. Conclusion: Channel assisted CKH-UBO for single segment CSR has the advantages of short operation time, reliable clinical effect, high safety and low complication rate, which is worthy of clinical promotion.